2020
DOI: 10.1002/lno.11441
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the dynamics of the deep hypolimnion of Lake Geneva as revealed by long‐term temperature, oxygen, and current measurements

Abstract: In order to identify or shed light on dominant long‐term processes of the deep hypolimnion of Lake Geneva (309 m depth), time series of temperature and horizontal currents and profiles of temperature and oxygen, taken for over a decade in the deepest part of the lake, were analyzed. The focus was on the summer stratification period (May to October). During that period, temperatures near the bottom always increased quasi‐linearly with the same gradient and small amplitude variability. Vertical mean temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 43 publications
5
26
0
Order By: Relevance
“…The spectra show a peak near the 12-13 h mark (inertial period) in both data and models. Such a period is most likely the signature of Poincaré waves and is consistent with the findings of (Lemmin, 2020;Lemmin et al, 2005). Fig.…”
Section: Resultssupporting
confidence: 87%
“…The spectra show a peak near the 12-13 h mark (inertial period) in both data and models. Such a period is most likely the signature of Poincaré waves and is consistent with the findings of (Lemmin, 2020;Lemmin et al, 2005). Fig.…”
Section: Resultssupporting
confidence: 87%
“…The inertial period at the latitude of Lake Geneva is approximately 16.5 hr. Numerous observational and numerical studies have shown that Coriolis force effects play an important role in determining the lake's hydrodynamics (e.g., Bauer et al, 1981; Bouffard & Lemmin, 2013; Cimatoribus et al, 2018, 2019; Lemmin, 2020; Lemmin et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…The ventilation of these deep layers is generally attributed to complete vertical overturning due to convective cooling during severely cold winters. Recently, it was shown (Lemmin, 2020) that (i) in cold winters, vertical DO profiles with a pronounced minimum in the bulk water of the deep hypolimnion persisting for several months and higher DO concentrations toward the lake bottom occur, suggesting the lateral advection of oxygen-rich water along the lakebed; (ii) a significant spatial variability of the DO concentrations in the near-bottom layer exists as revealed by measurements taken along submarine dive tracks across the central 300 m deep plateau in the Grand Lac basin; and (iii) an increase in DO levels at the deepest point of the lake (309 m) can be observed every year, even during mild winters with incomplete vertical convective mixing. Field measurements (Giovanoli, 1990) indicate that dense, sediment-laden turbidity currents from the lake's main tributary, the Rhône River, occasionally reach the deepest layers.…”
Section: Study Site Lake Genevamentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we focus on periods of lake cooling, when the lake water is above the temperature of maximum density ( T ≈ 4°C). The colder littoral region triggers density‐driven currents that transport littoral water downslope and intrude horizontally at the base of the surface mixed layer (e.g., Doda et al., 2022; Fer et al., 2001) or even at deeper depths for weak thermoclines, potentially contributing to deep water renewal (Biemond et al., 2021; Lemmin, 2020; Peeters et al., 2003). This particular type of density‐driven flow is called thermal siphons (Monismith et al., 1990) and has been viewed as an important mechanism connecting the littoral and interior regions during calm conditions in lakes (Fer et al., 2001; Woodward et al., 2017) and oceanic coastal waters (e.g., Shapiro et al., 2003).…”
Section: Introductionmentioning
confidence: 99%